The effect of calcium and magnesium ions in stimulating the transition to bacterial L forms - Aws Suleiman (College of Education for Pure Sciences, 1999)
Abstract The ability of Ca++ and Mg++ ions to induce the following bacterial species: Staphylococcus aureus, Klebsiella pneumoniae, Escherichia coli and Streptomyces albidoflavus to transform to L- forms were studied. Hypertonic special culture medium was designed for this purpose in which Vancomycin was added to it in concentration of (6.25 mg/l and 12.5 mg/l). The result indicated that the species Klebsiella pneumoniae was the most effective on especially at concentration of antibiotic Van. (12.5 mg/l) Also when we added MgSo4 alone at concentration of (0.5 gm/liter). The species Escherichia coli was clearly affected when we added CaCl2 alone to the medium at concentration of (3gm / liter) with availability of antibiotic at the same concentration above. The species Klebsiella pneumoniae at concentration of CaCl2 at (1.5 gm/liter) from the other was affected more than species under study. The same species Klebsiella pneumoniae was clearly affect when we added the both Ca++ and Mg++ ions in all concentration using but Escherichia coli was affected when we used MgSo4 (1 gm/liter) and CaCl2 (3 gm/liter) together from all other species. The species Klebsiella pneumoniae gave clear growth when we added antibiotic Van. At (6.25 mg / l) and at low percentage of MgSo2 (0.5 gm/ liter) and the species Escherichia coli didn't show any effect at concentration of MgSo2 (2 gm/ liter). The Klebsiella pneumoniae gave clear response at CaCl2 (12 gm/ liter) alone then the species Staphylococcus aureus but the species Escherichia coli didn't give any response. Best growth of L-form appears for the species Klebsiella pneumoniae when we added MgSo4 and CaCl2 together especially at concentration (4gm/ liter) for the 1st and (12 gm/ liter) for the 2nd one. So when we used the two salts at (0.5 and 4 gm/ liter) for MgSo4 and (1.5 and 12 gm/ liter) for CaCl2 we obtained the best culture medium for L- form and especially when we use MIC for antibiotic under study.